Robert W. Tebbs, Photographer to Architects : Louisiana Plantations in 1926 - Lewis, Richard Anthony, 1963- (Book collections on Project MUSE., 2011)
One of the finest architectural photographers in America, Robert W. Tebbs produced the first photographic survey of LouisianaAEs plantations in 1926. The images, now housed in the Louisiana State Museum, and never before widely available, consist of 110 plates showcasing fifty-two homes. Author and curator Richard Anthony Lewis explores TebbsAEs life and photographs, revealing in both a new awareness of historic preservation.